Discovery Learning Model Assisted by Tri Hita Karana as a Learning Resource for Ecological Literacy and Student Geography Learning Outcomes in High School - Astawa, Ida Bagus Made (LPPM Undiksha, 2022)
The objectives of learning geography have not been fully realized. One of the problems faced is that students feel learning is not exciting and boring. This study aims to analyze the effect of the Discovery Learning Model assisted by Tri Hita Karana's Learning Resources on Ecological Literacy and Student Geography Learning Outcomes. This type of research is experimental. The research used a quasi-experimental design with a Non-Equivalent Post-Test Only Control Group Design. The sample uses two classes from 4 classes that are assigned randomly after the equivalence test is carried out. The methods used to collect data are questionnaires and tests. Data collection instruments used test sheets and questionnaires. The data analysis techniques are descriptive qualitative analysis and quantitative and inferential statistics. The results showed an effect of the Discovery Learning Model assisted by Tri Hita Karana's Learning Resources on Ecological Literacy and Student Geography Learning Outcomes. It is evidenced by the significant difference in Ecological Literacy and Student Geography Learning Outcomes, partially or simultaneously, between classes that use and do not use the Tri Hita Karana Learning Resource Assisted Discovery Learning Model.